(Super)hydrophobic and Multilayered Amphiphilic Films Prepared by Continuous Assembly of Polymers. (16th May 2013) - Guntari, Stefanie N.; Khin, Aaron C. H.; Wong, Edgar H. H.; Goh, Tor K.; Blencowe, Anton; Caruso, Frank; Qiao, Greg G.
Abstract The continuous assembly of polymers (CAP) is used to fabricate tailored nanocoatings on a wide variety of substrates. Ring‐opening metathesis polymerization (ROMP) is used to mediate the CAP process (CAPROMP) to assemble specifically designed macromolecules into nanoengineered crosslinked films. Different films composed of single or multiple macromolecules are used to tune the surface wetting characteristics on various planar substrates, including porous substrates such as filter paper and cotton, and non‐porous subtrates such as aluminium foil and glass. By judicious selection of the macromolecules, these substrates, which are hydrophilic in nature, can be rendered (super)hydrophobic. The robustness of the ROMP catalysts and the reinitiation ability of the CAPROMP approach allow the production of layered multicomponent amphiphilic films with on‐demand switchable wettability. Such functional nanocoatings can be potentially applied as self‐cleaning surfaces, as waterproof woven fabrics, and for the next generation of microelectronic devices.